ХАРААТ ОРДЫН ГЕОЛОГИЙН ТОГТОЦ, СТРУКТУР - Б.БАТ; Л.АМАРТҮВШИН (Geological Issues, 2023)
Тhe рареr сопtains some results of the research work which is carried out by Company's geologists as one of the contents of the exploration project for Cu-Fe polymetalic skarn deposit. Kharaat Cu-Fe skarn deposit is located in Naranbulag soum, Uvs province, Mongolia. This paper is explane the geology, geochemistry, mineralogy of the Kharaat deposit which is aged as Lower Cambrian.